THE IMPLEMENTATION OF WEB-BASED E-CRM IN IMPROVING CUSTOMER SATISFACTION IN SMALL AND MEDIUM ENTERPRISES - Dhety Chusumastuti; Jamaluddin Majid; Brave Angkasa Sugiarso; Eva Desembrianita (Jurnal Sistem Informasi, 2023)
To enhance the services provided to small- and medium-sized business customers. Specifically for traditional retail enterprises and small and medium firms, take advantage of information and communication technology improvements that have emerged quickly but have yet to be applied well in the lower middle-class sector. They still need help to use and gain access to modern technology. Another connected issue is the tendency of consumer numbers to vary and decline as a result of the expansion of contemporary retail firms with vast and robust networks. This study will develop an electronic customer relationship management (e-CRM) program that can be used to support business operations to boost sales, and that makes it simpler for small and medium-sized firms to provide services.